Breast cancer incidence trends in Norway and estimates of overdiagnosis. (June 2017) - van Luijt, Paula A; Heijnsdijk, Eveline AM; van Ravesteyn, Nicolien T; Hofvind, Solveig; de Koning, Harry J
Objective: Fluctuations in the incidence of breast cancer in Norway in the last three decades are partly explained by the use of hormone replacement therapy and mammography screening, but overdiagnosis has also been suggested as a cause. We assessed the trends in breast cancer incidence and overdiagnosis in Norway. Methods: We calibrated our microsimulation model to Norwegian Cancer Registration data. The model takes into account the use of mammography (both within and outside the Norwegian Breast Cancer Screening Programme) and of hormone replacement therapy. We obtained a proper fit of breast cancer incidence in recent years, when assuming an increase in the background risk for breast cancer, and estimated overdiagnosis. Results: We estimated a 2% overdiagnosis rate as a fraction of all cancers diagnosed in women aged 50–100, and a 3% overdiagnosis rate as a fraction of all cancers diagnosed in women aged 50–70 (i.e. screening age). If all of the increased incidence would be the result of the detection of slow growing tumours, these estimates were 7% and 11%, respectively. Conclusion: Besides mammography and hormone replacement therapy use, additional risk factors contributed to the sudden increase in breast cancer incidence in Norway. Overdiagnosis estimates due to screening were within the range of international plausible estimates.